1998
DOI: 10.1161/01.cir.97.24.2414
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Denervation and Reinnervation After Arterial Switch Operation for Complete Transposition

Abstract: Cardiac sympathetic nerves were denervated early after and reinnervated late after ASO. Neonatal ASO may be favorable to facilitate sympathetic reinnervation, which may affect exercise tolerance late after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 30 publications
3
39
0
1
Order By: Relevance
“…However, two patients showed signs of denervation of the heart even 30 years after the ASO. This was consistent with the results of a previous study by Kondo et al A denervation of the heart was found early after the ASO and a reinnervation of various degrees later [6]. The present study had some limitations: the small sample size and the HRV which was only measured long time after the surgery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, two patients showed signs of denervation of the heart even 30 years after the ASO. This was consistent with the results of a previous study by Kondo et al A denervation of the heart was found early after the ASO and a reinnervation of various degrees later [6]. The present study had some limitations: the small sample size and the HRV which was only measured long time after the surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Changes in heart rate, HRV, and blood pressure are some of the variables that may reflect alterations in the balance between the sympathetic and parasympathetic nervous systems. Sympathetic denervation after TGA has been found early after the ASO, and reinnervation late after the surgery, using metaiodobenzylguanidine [6]. However, HRV is currently the method of choice for clinical assessment of denervation of the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kondo et al (14) reported that cardiac sympathetic nerves are reinnervated late after arterial switch operation. Similarly, it has been shown that one year after heart transplantation there was increased norepinephrine (NE) uptake, indicating reinnervation of cardiac sympathetic nerves (15).…”
Section: Discussionmentioning
confidence: 99%
“…*:Data are given as median (interquartile range) ‡ :P is calculated with Mann-Whitney U Test HF -power in the high frequency range -high frequency; LF -power in the low frequency range -low frequency; LF/HF -the ratio of low frequency to high frequency; NS -not significant; pNN50% -the percentage of successive normal sinus; R-R intervals longer than 50 milliseconds; rMSSD -root mean square of the successive normal sinus; R-R interval difference; SDNN -standard deviation of all normal sinus R-R intervals; TP -variance of all R-R intervals -total power; VLF -power in the very low frequency range -very low frequency. *:Data are given as median (interquartile range) † :P is calculated with paired samples t-test ‡ :P is calculated with Wilcoxon Signed Ranks Test (14) studied metaiodobenzylguanidine (MIBG) uptake in patients with complete transposition. They hypothesized that the heart was sympathetically denervated shortly after, and reinnervated late after the ASO.…”
Section: Discussionmentioning
confidence: 99%